Produção inicial do coqueiro anão verde sob diferentes lâminas e sistemas de irrigação - Silva, Janilson Barbosa da (2020)
Due to the industrialization of coconut water, there has been a significant increase in the demand for green coconut and the cultivated area of irrigated dwarf coconut in Brazil. Coconut is considered one of the fruit trees that most consume water in its irrigation. On the other hand, in recent years there has been a reduction in water availability for irrigation in several regions where coconut cultivation is an important economic activity. This situation made the rationalization of the use of water in irrigation of the coconut tree to be pointed out as mandatory. In this context, the study aimed to evaluate the effects of different irrigation depths, combined with irrigation systems and mulch on yield of young dwarf coconut plants. The experiment was conducted at the Curu Experimental Field, Embrapa Tropical Agroindustry, in the municipality of Paraipaba-CE. The experimental design was in randomized blocks with split-plot, in factorial 4 x 2 x 2, in strips with four irrigation depths (100%, 75%, 50% of ETc and 50% of ETc with partial drying of the root system (PRD)), two irrigation systems (drip and micro sprinkler), with and without mulch. Fruit yield, volume of coconut water per fruit, total soluble solids content, yield of coconut water and the irrigation water use efficiency were evaluated during twelve months. Deficit irrigation (75% ETc and 50% ETc) reduced fruit yield and coconut water yield compared to full irrigation (100% ETc). On the other hand, deficit irrigation increased the total soluble solids of coconut water and the irrigation water use efficiency in terms of fruits and coconut water. The irrigation with replacement of 75% of the ETc allowed to reach values of irrigation water productivity of 5.1 fruits and 2.4 L of coconut water per m3 of irrigation water applied. Irrigation with replacement of 50% of ETc allowed to reach values of irrigation water productivity of of 6.3 fruits and 2.6 L coconut water per m3 of water applied in the irrigation. Irrigation with 50% of ETc, and partial drying of the root system (PRD) did not show significant differences compared to the treatment that received the same irrigation amount for the evaluated variables. Drip irrigation showed averages of fruit yield, coconut water yield and irrigation water productivity, significantly higher than micro sprinkler irrigation, showing that it is a good alternative to increase the water use efficiency in coconut irrigation. The use of mulch did not influence the results obtained.